Empatyczne wspieranie i towarzyszenie dziecku z mutyzmem wybiórczym w środowisku edukacyjnym w świetle koncepcji Amication = Providing empathic support and accompanying the child with selective mutism in the educational environment in the light of the concept of Amication - Kos, Ewa Arleta; Matusiak-Rojek, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article attempts to reflect on the possibility of supporting students with selective mutism in the school environment. The main aim of the paper is to further our understanding of the nature of selective mutism in the context of the need to build a relationship with the student based on empathy and trust.
Keywords: selective mutism; supporting children with mutism; amicative issues; Amication pedagogy; mutyzm wybiórczy; wspieranie dzieci z mutyzmem; problematyka amikatywna; pedagogika Amication